AKA Shakespeare: A Scientific Approach to the Authorship Question by Peter A. Sturrock - Spittle, Bruce (Journal of Scientific Exploration, 2014)
Peter Sturrock’s innovative book provides not only an original statistical approach to the Shakespeare authorship question but also an opportunity, by use of an associated website, for the reader to calculate for himself or herself the probability of who the most likely author was. Peter Sturrock, founder of the Society for Scientific Exploration, President of the Society from 1981 to 2001, and Editor-in-Chief of this journal in 2008, has had a distinguished career in astrophysics and is Emeritus Professor of Applied Physics and Emeritus Director of the Center for Space Science and Astrophysics at Stanford University. His interest in the authorship question arose a few years ago when he recalled that in his youth he wrote a poem beginning, “Shall I compare thee to a winter’s night?” which parodied the sonnet starting with “Shall I compare thee to a summer’s day?” He then reread the famous sonnet, the adjacent ones, and then the entire sequence. This led him to wonder who wrote them, to whom they were addressed, and what they were all about. When he assumed the author was William Shakspere of Stratford-upon-Avon, he could find no sensible answers to the other two questions, despite reading books by Shakespeare scholars. He found that many arguments were presented by both the Shakspere-Is-Shakespeare advocates and the Shakspere-Is-Not-Shakespeare dissenters but that no one argument, either way, was conclusive. Eventually he realized that the question could best be resolved by weighing and combining many different pieces of evidence using a process he had thought about for some years and had developed into a method for studying pulsars.